Analisis Dampak Covid-19 terhadap UMKM di Kabupaten Batang Hari - Muryati Muryati; Atti Rasnawati; Adli Azhari (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2022)
This research is focused on the Impact of Covid-19 on Micro, Small and Medium Enterprises and Strategies for UMKM to survive during the Covid-19 period. This is done to find out how the impact of Covid-19 on UMKM in Batang Hari Regency and at the same time how UMKM strategies to survive during the Covid-19 period. The research method used is descriptive qualitative research method, with data collection techniques in the form of interviews with business actors and from several sources of other articles. The results of this study indicate that there are 2 impacts of Covid-19 on UMKM in Batang Hari Regency, including negative impacts and positive impacts. From the results of interviews conducted with 99 MSME actors consisting of 3 types, namely Culinary UMKM, Fashion UMKM and Agribusiness UMKM, it shows that during the Covid-19 period, 79% of UMKM in Batang Hari Regency experienced a negative impact, while 21% of UMKM in Batang Hari Regency experience a positive impact. Then there are several strategies carried out by MSME actors such as providing good service to consumers and paying attention to the quality of goods to be sold to consumers, carrying out health protocols in doing business, trading through social media and applying for capital assistance to the government